2012
DOI: 10.3324/haematol.2012.072835
|View full text |Cite
|
Sign up to set email alerts
|

Functional invariant natural killer T-cell and CD1d axis in chronic lymphocytic leukemia: implications for immunotherapy

Abstract: ABSTRACTactive malignancy or previous chemotherapy for a disease other than CLL. All donors gave written informed consent. Ethical approval for the study was obtained from the Central Regional Ethics Committee of New Zealand.Binet and Rai prognostic scores were determined from the clinical examination and absolute differential blood counts (Sysmex XE 2100 analyzer, Roche Diagnostics, Auckland, New Zealand) measured at the time of blood sampling. Details of peripheral blood mononuclear cell (PBMC) isolation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 49 publications
2
36
1
Order By: Relevance
“…It is important to note that iNKT cells have recently been revealed as a one of key players in the immune responses against tumors [34] and their numbers and function were found to be normal in patients with CLL in early stages [35]. Our results suggest that that progression of CLL is associated with downregulation of Th17 cells and expansion of Treg cells.…”
Section: Discussionmentioning
confidence: 52%
“…It is important to note that iNKT cells have recently been revealed as a one of key players in the immune responses against tumors [34] and their numbers and function were found to be normal in patients with CLL in early stages [35]. Our results suggest that that progression of CLL is associated with downregulation of Th17 cells and expansion of Treg cells.…”
Section: Discussionmentioning
confidence: 52%
“…iNKT cells that we have recently reported [5]. Knowing that several tumours use CD1d downregulation to evade immune detection [9][10][11][12], we examined whether cell surface CD1d was modified in CML-CP mDCs.…”
Section: In Vitro Differentiation Of Mature Mdcs From Blood Monocytesmentioning
confidence: 99%
“…[19][20][21] In CLL patients, it was reported that CD1d expression by malignant cells correlates with adverse prognosis, whereas iNKT cells can recognize leukemia cells in vitro when preloaded with synthetic a-GalCer. [22][23][24] However, the role of iNKT cells in the natural history of CLL is essentially unknown.…”
Section: Introductionmentioning
confidence: 99%